Effects of Extended-Release Niacin on Quartile Lp-PLA2 Levels and Clinical Outcomes in Statin-treated Patients with Established Cardiovascular Disease and Low Baseline Levels of HDL-Cholesterol: Post Hoc Analysis of the AIM HIGH Trial. (November 2019) - Lyubarova, Radmila; Albers, John J.; Marcovina, Santica M.; Yao, Yao; McBride, Ruth; Topliceanu, Alexandru; Anderson, Todd; Fleg, Jerome L.; Desvigne-Nickens, Patrice; Kashyap, Moti L.; McGovern, Mark E.; Boden, William E.
Background: Lipoprotein-associated phospholipase A2 (LpPLA2 ) is an inflammatory marker that has been associated with the presence of vulnerable plaque and increased risk of cardiovascular (CV) events. Objective: To assess the effect of extended-release niacin (ERN) on Lp-PLA2 activity and clinical outcomes. Methods: We performed a post hoc analysis in 3196 AIM-HIGH patients with established CV disease and low baseline levels of high-density lipoprotein cholesterol (HDL-C) who were randomized to ERN versus placebo on a background of simvastatin therapy (with or without ezetimibe) to assess the association between baseline Lp-PLA2 activity and the rate of the composite primary end point (CV death, myocardial infarction, stroke, hospitalization for unstable angina, and symptom-driven revascularization). Results: Participants randomized to ERN, but not those randomized to placebo, experienced a significant 8.9% decrease in LpPLA2 . In univariate analysis, the highest quartile of LpPLA2 activity (>208 nmol/min/mL, Q4) was associated with higher event rates compared to the lower quartiles in the placebo group (log rank P = .032), but not in the ERN treated participants (log rank P = .718). However, in multivariate analysis, adjusting for sex, diabetes, baseline LDL-C, HDL-C, and triglycerides, there was no significant difference in outcomes between the highest Lp-PLA2 activity quartile versus the lower quartiles in both the placebo and the ERN groups. Conclusion: Among participants with stable CV disease on optimal medical therapy, elevated Lp-PLA2 was associated with higher CV events; however, addition of ERN mitigates this effect. This association in the placebo group was attenuated after multivariable adjustment, which suggests that Lp-PLA2 does not improve risk assessment beyond traditional risk factors.